2005
DOI: 10.1063/1.1870852
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the structure of amorphous ice: From low-density amorphous through high-density amorphous to very high-density amorphous ice

Abstract: We report results of molecular dynamics simulations of amorphous ice for pressures up to 22.5 kbar. The high-density amorphous ice (HDA) as prepared by pressure-induced amorphization of I h ice at T = 80 K is annealed to T = 170 K at various pressures to allow for relaxation. Upon increase of pressure, relaxed amorphous ice undergoes a pronounced change of structure, ranging from the low-density amorphous ice (LDA) at p = 0, through a continuum of HDA states to the limiting very high-density amorphous ice (VHD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
83
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 62 publications
13
83
0
Order By: Relevance
“…However, the topological differences in the underlying hydrogen bond networks observed here is striking and consistent with the presence of a first-order phase boundary between the amorphous phases of ice, as noted in Ref. 100,101 . Furthermore, this finding complements the distinctive features of HDA and LDA observed via the g OO (r) above.…”
Section: Signature Of Polyamorphism In the Ipes Of Ambient Liquid supporting
confidence: 59%
See 3 more Smart Citations
“…However, the topological differences in the underlying hydrogen bond networks observed here is striking and consistent with the presence of a first-order phase boundary between the amorphous phases of ice, as noted in Ref. 100,101 . Furthermore, this finding complements the distinctive features of HDA and LDA observed via the g OO (r) above.…”
Section: Signature Of Polyamorphism In the Ipes Of Ambient Liquid supporting
confidence: 59%
“…All P(N ) were normalized to unity and therefore do not reflect the total number of rings of a given size. P(N ) of low-and high-density-like clusters bears strong similarities with those found for the LDA and HDA ice phases 100,101 . Instead of a predominance of N = 6 membered rings, as expected in the structures of LDA 100,101 , we found that the largest majority of rings contain N = 5 members with significantly large populations of smaller rings among the high-and low-density-like water molecules in the IPES of ambient liquid water.…”
Section: Signature Of Polyamorphism In the Ipes Of Ambient Liquid supporting
confidence: 48%
See 2 more Smart Citations
“…Both ice 0 and ice i are significantly more stable (∼40 meV/molecule at the PBESOL-D3 level, configuration taken from Ref. 46) than low density amorphous ice, which is of comparable density to ice 0 and ice i, suggesting that ordered structures may be more effective at mediating the nucleation of ice I h . …”
Section: Discussionmentioning
confidence: 99%